KOMUNIKASI INTERPERSONAL KIYAI DALAM MENINGKATKAN SIKAP RELIGIUSITAS SANTRI MELALUI TRADISI SOWAN - Mia Nurislamiah; Rifki Fauzi; Hani Fatul Muzayyanah (Communicative : Jurnal Dakwah dan Komunikasi, 2023)
Abstract : Pondok Pesantren is a traditional Islamic educational institution in Indonesia which has an important role in religious education and the formation of the character of students. Interpersonal communication between the Kiayi (founder or leader of the pesantren) and the santri is very important in building close relationships and mutual understanding. Kiayi have strong authority and influence in guiding and fostering santri. Through the sowan tradition it becomes a means for direct communication and provides personal religious teachings and spiritual advice. Improving the religious attitude of the santri is the main goal, and interpersonal communication through the sowan tradition is expected to motivate, inspire and assist the santri in their daily religious practices. This study aims to determine the sowan tradition at the Khas Kempek Putri Islamic Boarding School Al Nashir Al Manshur, to find out the verbal and non-verbal communication of clerics in increasing the religiosity of students through the sowan tradition at the Khas Kempek Putri Islamic boarding school, Asrama Al Nashir Al Manshur. The research methodology uses qualitative methods with a descriptive approach. The data source for this research was obtained from interviews with several informants including Kiayi and Santri at the Islamic boarding school Khas Kempek Putri Asrama Al Nashir Al Manshur. Data collection techniques were taken through observation, interviews and documentation. Besides that, the data were analyzed by the steps of data collection, data reduction, data display and drawing conclusions. The results of this study indicate that the kiai's interpersonal communication through the sowan tradition has an important role in increasing the religious attitude of the santri. The kiai's verbal communication can provide proper religious understanding and advice to the santri, while the kiai's nonverbal communication can help the santri understand religious values better. Keywords: Interpersonal Communication, Kiayi, Religious Attitude, Santri, Sowan